2019
DOI: 10.1016/j.esxm.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Soy Isoflavone Improved Female Sexual Dysfunction of Mice Via Endothelial Nitric Oxide Synthase Pathway

Abstract: Introduction Female sexual dysfunction (FSD) is a common endocrine disease that impairs the quality of life for many women. The existing therapy strategies still have many disadvantages. It is necessary to explore new pharmacologic treatments that are effective and safe. Aim The aim of this study was to explore the effects of soy isoflavone (SI) on FSD in mice and the underlying mechanisms. Methods and Main Outcome Measures Laser Doppler flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The estrogen levels and the number of mature follicles significantly increased in isoflavone fed mice, suggesting that isoflavones promote the maturation of ovarian follicles [265]. In addition, isoflavone dose-dependently improved sexual dysfunction by activating the endothelial nitric oxide synthase (eNOS) signaling pathway via the estrogen receptor [265]. This shows that isoflavones in soybeans could improve sexual function in middle-aged female mice and confirms its potential for treating sexual dysfunction.…”
Section: Enhanced Quality Of Life For Postmenopausal Women Based On Improved Physical and Emotional Symptomsmentioning
confidence: 70%
See 2 more Smart Citations
“…The estrogen levels and the number of mature follicles significantly increased in isoflavone fed mice, suggesting that isoflavones promote the maturation of ovarian follicles [265]. In addition, isoflavone dose-dependently improved sexual dysfunction by activating the endothelial nitric oxide synthase (eNOS) signaling pathway via the estrogen receptor [265]. This shows that isoflavones in soybeans could improve sexual function in middle-aged female mice and confirms its potential for treating sexual dysfunction.…”
Section: Enhanced Quality Of Life For Postmenopausal Women Based On Improved Physical and Emotional Symptomsmentioning
confidence: 70%
“…A study analyzed serum hormone levels, vaginal histological changes, and enzyme-linked immunosorbent assays in mice to confirm the effect of isoflavone on female sexual function and the underlying mechanisms. The results indicated that vaginal blood flow was significantly lower in the adult mice of the control group than in the mice that were fed isoflavone, in response to pelvic nerve stimulation in a dose-dependent manner [265]. The estrogen levels and the number of mature follicles significantly increased in isoflavone fed mice, suggesting that isoflavones promote the maturation of ovarian follicles [265].…”
Section: Enhanced Quality Of Life For Postmenopausal Women Based On Improved Physical and Emotional Symptomsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, consumption of soy, a phytoestrogen, is shown to support increased vaginal blood flow, lubrication, and vaginal collagen content and decreased dyspareunia. [45][46][47] As a suppressor of free-radical generation, the benefits of soy plausibly include an antiinflammatory effect that enhances NO activity. 45,48 Fruits such as apples, watermelon, and cacao have been linked to enhanced vascular and sexual health.…”
Section: Sexual Healthmentioning
confidence: 99%
“…[45][46][47] As a suppressor of free-radical generation, the benefits of soy plausibly include an antiinflammatory effect that enhances NO activity. 45,48 Fruits such as apples, watermelon, and cacao have been linked to enhanced vascular and sexual health. Daily apple consumption is associated with improved vaginal lubrication and general sexual function.…”
Section: Sexual Healthmentioning
confidence: 99%